Implications of Digital Marketing Strategy The Competitive Advantages of Small Businesses in Indonesia - Katoyusyi Kano; Lee Kyung Choi; Bob subhan Riza; Regina Dinda Octavyra (Pandawan Sejahtera Indonesia, 2022)
In the current era of technology, it provides many impacts and innovations that can provide more effective solutions in various fields. With digital marketing as an alternative solution, digital marketing can now overcome problems such as lack of funds and limited promotions faced by medium to low-income businesses. The alternative solution is obtained with the current social media such as Twitter, Instagram, Website, and Facebook to create brand awareness, loyalty, sales, and engagement. So the purpose of this study is to find out the use of marketing strategies from several lower-middle businesses that have gone online and their implications for the competitive advantage of these lower-middle businesses. The method used in this study uses quantitative methods with causality analysis with a population of more than 21,000,000 consumers using a non-probability sampling technique using random sampling with a total sample of 2,100 respondents. So based on the research that has been done, it was found that in marketing products with a digital strategy, 78% of the results were obtained, with the remaining 22% being factors originating from other factors such as a supply of resources, capital, and managerial professionalism.